Local treatment of liver metastases by administration of 177Lu-octreotate via isolated hepatic perfusion – A preclinical simulation of a novel treatment strategy. (June 2019) - Sandblom, Viktor; Ståhl, Ingun; Hansson, Christoffer; Olofsson Bagge, Roger; Forssell-Aronsson, Eva
Abstract: Introduction: Systemic 177 Lu-octreotate treatment for metastatic neuroendocrine tumours is restricted by organs at risk. By administering 177 Lu-octreotate during isolated hepatic perfusion (IHP), the uptake in organs at risk might be strongly reduced. The aim of this study was to investigate the feasibility to use the combination of IHP and radionuclide therapy. Methods: To simulate IHP, the liver of a pig was prepared for ex vivo perfusion. Blood containing 490 MBq 177 Lu-octreotate was circulated through the liver for 60 min, after which the liver was rinsed. After IHP, the liver was examined by SPECT/CT. Lastly, an intraoperative gamma detector (IGD) was used to determine 177 Lu activity concentration in the liver and results were compared with the activity concentration in corresponding liver biopsies. Results: Detector measurements over the liver during the IHP showed a fast increase with a maximum after approximately 10–15 min. After IHP, about 75% of the 177 Lu in the liver could be washed out. The SPECT/CT images revealed a relatively inhomogeneous distribution. Nevertheless, the IGD values of 177 Lu activity concentration showed acceptable agreement with the biopsy values. Conclusions: Our results in pig show that it could be feasible to treat patients with liver metastases from NETs with 177 Lu-octreotate via IHP 177 . However, an inhomogeneous distribution of 177 Lu-octreotate in normal liver tissue is expected, and in order to determine the activity concentration with satisfactory accuracy using an IGD, measurements need to be performed at several positions over the liver. Highlights: Isolated hepatic perfusion with 177 Lu-octreotate was successfully simulated in a pig. A relatively inhomogeneous uptake of 177 Lu-octreotate in the liver was obtained. About 25% of the 177 Lu-octreotate in the liver remained after rinsing. An intraoperative gamma detector could be used to quantify 177 Lu-octreotate in vivo . Radiation exposure of the staff involved could be kept below regulatory dose limits.